Necesidad de reformar el art. 81 de la ley orgánica de la policía nacional incorporando un procedimiento para garantizar el derecho a la defensa del policía ante el tribunal de disciplina - Buele Satama, Fabian Leonardo (2015)
This thesis was carried out because the Article 81 of the Organic Law of the National Police, only states: "The Disciplinary Tribunal has the power to adjudicate disciplinary offenses under the relevant Regulations and in accordance with the procedure outlined in myself", more in the Regulation in question only stated in general conducting a hearing on disciplinary offenses and even third-class appeal and Resolution of the Court of Discipline enforceable because it does not allow a situation that threatens the right to blatantly defense and due process constitutionally established. Developing the right to legal security guaranteed in Article 82 of the Constitution of the Republic of Ecuador, and still the Law of the National Police, organic nature, its regulations must contain a specific procedure for sanction before the Court of discipline clear procedural rules that tend to develop due process and all warranties. In this research show that I then need to be incorporated in the Organic Law of the National Police oral proceedings governing the prosecution and punishment by the Disciplinary Tribunal to the members of the National Police. I hope the research will be useful for other members of the National Police who will benefit from this, my research.